Permian flood basalt protoliths for Jurassic amphibolites and eclogites in SW Iran: implications for subduction of a magma-rich passive margin - Jamali Ashtiani, Rezvaneh; Schmitt, Axel Karl; Hassanzadeh, Jamshid; Sharifi, Arash; Günter, Christina (Lithos, 2024)
Magma-rich passive margins are characterized by mafic intrusions and lavas, making their density comparable to that of the adjoining oceanic crust. As a result, these margins may sink along with the oceanic crust when subduction begins. This possibility warrants further investigation in the geologic record. A fitting example can be found in the Sanandaj-Sirjan Zone (SaSZ), north of the Neotethyan Zagros suture in Iran, where amphibolite to eclogite-facies metabasites are exposed in the Zayanderud high-pressure metamorphic complex. We present UPb zircon ages, whole rock elemental analyses, and Sr-Nd-Hf isotope data to constrain the ages, chemical and isotopic composition, as well as the tectonic setting of the metabasite protoliths. Ion microprobe UPb zircon geochronology on petrographic thin sections reveals Early-Middle Permian protolith ages for small (≤10 μm in diameter) zircon crystals that have been metamorphically overgrown in the eclogite. The elemental and Sr-Nd-Hf isotopic compositions of eclogites and amphibolites indicate a continental flood basalt affinity. Trace element and isotopic signatures closely resemble those of widespread Permian flood basalts erupted during breakup of Pangea and the opening of the Neotethys Ocean, with well-studied examples from Oman, the Himalayas, and the Asian Large Igneous Provinces in Tarim, Tianshan, and Emeishan. Earlier investigations suggested that the eclogitization occurred in the Early-Middle Jurassic. Our findings support a scenario where a magma-rich passive margin was established during the Permian and subsequently sank into the mantle at the onset of Jurassic subduction along this segment of the Neotethys. This studied example advocates a poorly explored possibility of the deep sinking of magma-rich passive margins at the beginning of subduction.
Gesehen am 11.07.2025